Increasing Students’ Learning Outcomes Through the Script Model of Cooperative Learning in Secondary School - Sitti Kasmiati; Surdin Surdin; La Ode Amaluddin; Vida Evi Lestari (STAI Hubbulwathan Duri, 2023)
This study aims to improve student learning outcomes majoring in Social Sciences at Wawotobi High School through the application of scripted cooperative learning. This learning model is applied to determine student learning outcomes on the topic of Indonesian Natural Resources Management because students are less active during learning and are always teacher-centred, especially in student collaboration activities. The experimental research method used in this study was a one-group experimental design. This research includes pre-test and post-test. It was carried out at Wawotobi State High School in the 2021-2022 academic year. Participants were taken from the social studies major in third grade. That's about 30 students. Data collection methods include observation, tests, and documentation. The data findings conclude that t-stat t-table (-21.973 2.045), so it can be said that cooperative learning through a script model significantly increases the overall value of student learning outcomes. Learning outcomes on the subject of population dynamics in Indonesia have increased and 30 students have met the Minimum Completeness Criteria scores with a percentage of completeness learning outcomes is 100%. The results of this study recommend teachers apply a script-type cooperative learning model as alternative learning that can be done online and offline. The results of this study also have implications for teachers' understanding of the learning approach that should be used according to the needs and characteristics of students or the learning objectives to be achieved.